2022
DOI: 10.12998/wjcc.v10.i22.7913
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric reticulohistiocytosis with prominent skin lesions and arthritis: A case report

Abstract: BACKGROUND Multicentric reticulohistiocytosis (MRH) is a rare non-Langerhans histiocytosis of unknown etiology characterized by papulonodular skin lesions and progressive, erosive arthritis. To date, there have been approximately 300 cases of MRH reported worldwide. The majority of patients are Caucasian from western countries, and Asian patients are rare. Here, we report a case of MRH in a Chinese patient. CASE SUMMARY A 38-year-old male was admitted to the hospital wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Skin nodules of MRH have a characteristic coral bead appearance and are more often observed around the ungual region and may also be observed on the mucosa, face, arms, and torso. Facial lesions were described as having a lion-like appearance in the literature [ 8 ]. Systemic MRH may present as pleural and pericardial effusion (Figures 5 , 6 ), congestive heart failure, urogenital lesions, and mesenteric lymphadenopathy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Skin nodules of MRH have a characteristic coral bead appearance and are more often observed around the ungual region and may also be observed on the mucosa, face, arms, and torso. Facial lesions were described as having a lion-like appearance in the literature [ 8 ]. Systemic MRH may present as pleural and pericardial effusion (Figures 5 , 6 ), congestive heart failure, urogenital lesions, and mesenteric lymphadenopathy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, multinucleated giant cells and histiocytes are seen with eosinophilic ground glass cytoplasm. These cells stain positive for periodic acid-Schiff (PAS), CD163, HAM56, and CD68 and negative for Langerhans markers such as S-100, CD1a, CD19, and CD20 [ 7 , 8 ]. Recent studies have demonstrated positive Mac387, vimentin, CD43, CD45, and lysozyme in a few patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations